Oral literature as an index of social change among the Bagisu and Ba nyankole - Mwambu, Esther (Kampala, 1998)
Thesis (M.A., Literature) - Makerere University, 1998
Includes bibliographical references (p.169-171)
Keywords: Folk literature, African -- Uganda